Propuesta de creación de una ruta gastronómica: El camino del ceviche ecuatoriano a través de las provincias de Pichincha, Esmeraldas y Manabí - Valencia Cifuentes, Nicole Alejandra (2016)
During the last few years, tourism has been an important part for the economic growth of underdeveloped countries, and Ecuador is not the exception. Thanks to the natural and cultural diversity present in the country, some projects have been developed in order to promote tourism. However, achieving sustainable development, something that is crave in the industry, has been left in a speech and is not a reality. The food heritage is one of the cultural attractions with more potential, although, it has not been fully developed in Ecuador. Through the study of: products, ingredients and cooking methods in different places related with the elaboration of the traditional ceviche, it has been stablished strategic points that have a lot of tourist-gastronomic potential in provinces of: Pichincha, Esmeraldas and Manabí. The tourists have the opportunity to enjoy and learn about aspects of each place. Giving rise a gastronomic route as an alternative or complementary tourist offer, which mainly benefits one of the most vulnerable sectors: the artisanal fishing. This project also represents a compilation of information related with native and introduced products that are part of the daily diet of Ecuadorians and are used in the preparation of ceviche The gastronomic route represents an alternative for tourists and representing an opportunity for the economic development of the selected location.